Consumer Behavior Regarding Usage Of Food Ordering Applications In And Around Chandigarh - Sharma, Neeraj; Saraf, Kanav (Gyan Management Journal, 2020)
Significance of utilizing the Internet in marketing mixes is being recognized by numerous marketers.  But only few researchers has experimentally tested the critical variables that impact an individual's  decision while purchasing items or services on the web. Based on the aperture in the literature, the  motive of the study is to comprehend the impression of Electronic Online Food Ordering. The main  consideration that represses the person who has never ordered anything through web is a mental  barrier regarding usage of Internet for Food Ordering and discomfort in using the apps on mobile for  food ordering. Another reason for not ordering food through internet is fear of hacking of financial  data  or  its misuse.  Consumers' Perceptions  of Online Ordering  varies from  person to  person. The  intention  of this  research  work  is to  help  food service  providers to  better  design their  electronic  ordering channels. The most significant attribute while ordering on web is order exactness. After that it  is convenience and simplicity of placing an order. Telephone calls are most widely recognized medium  for placing an order, in spite of availability of the internet and phone apps. Electronically placing an  order is developing; however the respondents said they place little more than 38 percent of their orders  on the restaurant's website or app. A main ramification is that restaurateurs should give guarantee  that their ordering systems give impression of control and convenience to the user. Another factor that  needs to be focused is that clients prefer restaurants with home delivery service for online ordering. It is  found in this research that there is a growing tendency among youth to order food only more frequently  through online apps available on Mobile phones.
Keywords: Online Food Ordering; e-wallet; Consumer Perception